INTEGRASI NILAI SYARIAH DALAM BENCHMARKING PEMBIYAYAAN PENDIDIKAN: BERBANDING ANTARA SISTEM ISLAM DAN KONVENSIONAL - Saifullah; Ridho Apriyadi; Subandi; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education financing is an important aspect of sustainable human resource development. In Indonesia, there are two dominant education financing systems, namely the Islamic education system and the conventional education system. Each system has different financing principles and models, which affect the effectiveness and efficiency of the use of education funds. This research aims to examine the integration of sharia values in education financing benchmarking, and compare the strengths and weaknesses of each system. Using a descriptive-qualitative approach through a literature study, data was collected from academic journals, institutional reports, and education statistics. The research found that the Islamic education system has advantages in terms of social justice and sustainability, while the conventional system excels in aspects of technology management and variety of scholarship schemes. This research provides strategic recommendations for Islamic education institutions to adopt best practices from the conventional system without ignoring sharia principles.